Lp(Lq)-Maximal Regularity for Damped Equations in a Cylindrical Domain - Lizama-Yanez, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
We show maximal regularity estimates for the damped hyperbolic and strongly damped wave equations with periodic initial conditions in a cylindrical domain. We prove that this property strongly depends on a critical combination on the parameters of the equation. Noteworthy, our results are still valid for fractional powers of the negative Laplacian operator. We base our methods on the theory of operator-valued Fourier multipliers on vector-valued Lebesgue spaces of periodic functions. © 2024 by the authors.